A Comprehensive Review of Homepreneurs in the Digital Era - Srivastava, Pooja; Sharma, Meenal (AMC Indian Journal of Entrepreneurship, 2020)
In today’s competitive environment, businesses are reaching homes and are creating homepreneurs. Home-based businesses are now a substantial part of the small business sector and account for an increasing proportion of business start-ups. In India, homepreneurs were largely defined by women because for ages, Indian women were bound by societal pressures and thus, were restricted from moving out for employment opportunities. So, they resorted to becoming homepreneurs. With government policies, globalization and development of entrepreneurial spirit, not only millennials but the middle age women and men are becoming imminent entrepreneurs. Digitalization in business processes has redefined the concept of homepreneurs in India. In the era of challenging customers, circadian changing buying behavior and integration of technology acceptance among customers, the concept of home based businesses has changed. This study comprehends and explores the concept of homepreneurs in India. The study identifies the salient characteristics of homepreneurs and their businesses and addresses the level of digitalization in home based businesses, its effects, and the proposal of an agenda for the future. Home-based online business ventures are an increasingly universal, yet an under-researched phenomenon. The study provides better experiences, understanding and creates a mind-set of businesspersons for setting up and running such enterprises.